Síndrome metabólica e seus fatores associados em indivíduos adultos - Freitas, Taciane Oliveira Bet (2015)
Metabolic syndrome is a set of changes consisting of dyslipidemia, glucose intolerance, hypertension, obesity and hyperinsulinemia. The study of this syndrome is of great importance to public health, since it can lead to negative outcomes that could increase their risk of cardiovascular disease in the general population. OBJECTIVE: Investigate the occurrence of metabolic syndrome and associated factors in adults treated in public health services in the city of Feira de Santana - BA. METHOD: epidemiological study, cross-sectional and exploratory conducted in 479 adults aged at least 20 years, seen at public health services in the fair city of Santana - BA. Information was obtained through structured questionnaires, anthropometric clinical and oral, and biochemists. The diagnosis of metabolic syndrome took into account the criteria proposed by the National Cholesterol Education Program - Adult Treatment Panel III / (NCEP-ATP III) and the International Diabetes Federation (IDF). Prevalence ratios were estimated (PR) and their respective confidence intervals of 95% (95% CI) and statistical significance level of 5%. Multivariate analysis was constructed using Poisson regression. RESULTS: Presented in the form of a scientific paper: "Metabolic syndrome and its associated factors in adults", to be submitted to the Journal Brazilian Archives of Endocrinology and Metabolism. The occurrence of MS ranged from 57% (NCEP / ATP III) to 62% (IDF). In the bivariate analysis female, advanced age, overweight, and some comorbidities proved to be independently associated with MS. In the hierarchic analysis, only BMI ≥ 30 kg / m² (NCEP-ATPIII) and no measurement of blood pressure periodically (IDF) remained independently associated with metabolic syndrome. CONCLUSIONS: The metabolic syndrome is a public health problem among individuals in this study. The body mass index ≥ 30 kg / m2 not regular blood pressure measurements are important predictors of the metabolic syndrome in adults.